Adjustment problems of students boarders and non-boarders of Baguio City High School - Gazmen, Nancy M. (Nancy Menecio) 1948-
The primary purpose of this study was to identify adjustment problems of the student boarders and non-boarders of Baguio City High School enrolled during the school year 1981-1982. Furthermore, it compares the academic achievement of the respondents. The effect of year level and geographic origin on adjustment, personality and achievement is investigated. Lastly, the relationship of adjustment to personality and academic achievement is determined.